SISTEM KENDALI KEKERUHAN DAN pH AIR KOLAM BUDIDAYA IKAN NILA - Pulungan, Ali Basrah; Putra, Aditya Manggala; Hamdani, Hamdani; Hastuti, Hastuti (ELKHA : Jurnal Teknik Elektro, 2020)
This study aims to make a tool that can monitor the condition of the pH level and water turbidity in fish ponds so that fish growth can be maximized. This fish pond has a control system that can be controlled automatically. The purpose of using this control is to get maximum results and to save water use in fish ponds This tool has two sensors consisting of a TDS-10 sensor which functions to detect the turbidity level of water in fish ponds and a pH sensor which functions to detect the pH level of the water in the fish pond. Comparison with previous research, the application of fish ponds with a size of 3 x 4 meters so that observations about how the tools work and the success rate of the tools can be observed more intensively. In addition, the ESP8266 wifi module is supported as a collaboration monitoring center without the need to come to the location directly Based on the test results of the TDS-10 sensor and pH sensor that have been carried out in the fish pond, the test results show good performance with the proportion of detection error of the TDS-10 sensor (4.8 NTU) to the set point (5 NTU) is 4%.